PEMANFAATAN KOMPRESOR UDARA UNTUK MENINGKATKAN PELAYANAN BAGI PENGGUNA JASA BENGKEL SEPEDA MOTOR - Zumhari, Zumhari; Asriyati, Asriyati; Suherman, Suherman; Sari, Dewi Comala; Safitri, Habibi Ramdani (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2024)
The community service activity carried out in Sumber Mulyorejo Village, Binjai Timur Subdistrict, for business partners in the field of motorcycle repair technology is a collaboration between higher education institutions and the community to fulfill the requirements of the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education). This collaboration emphasizes technology transfer and ensures the availability of technology needed by the community. As part of this planned community service initiative, the technology transfer from the proposing team to the business partners also includes providing and enhancing the technical equipment already owned by the partners. In running their motorcycle repair businesses, the partners face challenges due to the limited equipment they possess. The incompleteness and simplicity of the technical equipment owned by the partners result in slow and low-quality completion of work for their customers. Several complaints have been raised by customers with the partner regarding the slow completion of work. As a result, the number of customers has decreased. If this situation continues to recur, there is a possibility that the partner may lose customers entirely, which would inevitably reduce the partner's income. To address this detrimental situation, improving and adding technical equipment have become necessary and an urgent priority. The outcomes of this community service activity include an increase in the partner's income in the workshop sector and the addition of new equipment, namely one air compressor unit and tools supporting motorcycle service and repair work.